ANALISIS KESESUAIAN ANTARA RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MAHASISWA PPL IPAI 2016 DENGAN STANDAR PROSES PENDIDIKAN DALAM PERMENDIKBUD NO. 22 TAHUN 2016 - Rosmiati Nurhalimah, - (2020)
ABSTRACT Teachers are required to make a learning implementation plan (RPP) because it is one of the important things and at the same time it is the teacher's job as a Law No. 14 of 2005. But the reality shows that there are still many teachers who haven't met the process standard. As prospective teachers, college students who practice for having experience (PPL) before practicing teaching in class must be able to prepare lesson plans in accordance with the educational process standards in Permendikbud No. 22 of 2016. Researchers' activities in assessing the ability of PPL IPAI 2016 college students in compiling RPP are very important in the series of research. Therefore the objectives of this research are: (1) to analyze the components of the PPL IPAI 2016, (2) to analyze the suitability between the components of the PPL IPAI 2016 college student lesson plans with the educational process standards in Permendikbud No. 22 of 2016,This research uses a qualitative approach with descriptive methods. Collecting data using documentation techniques which are then analyzed through the stages of data reduction, data display, and verification. The results of this research indicate that. Of the twenty-three lesson plans for PPL IPAI college students in making eleven aspects of the components, there are still many lesson plans that do not match the components of identity, time allocation, learning objectives, basic competencies and indicators of competency achievement, learning methods, learning steps, and assessment steps are not in accordance with the educational process standards. Keywords: Standard Process, Permendikbud, RPP Components